REPRESENTASI TEMA INDUSTRIAL PADA TOKO RAILROAD INDUSTRIAL FURNITURE - Persada, Nyoman Gema Endra; Puspita Giri, Kadek Risna; William Nata Pradnya, I Putu (SENADA (Seminar Nasional Manajemen, Desain dan Aplikasi Bisnis Teknologi), 2020)
Buildings with commercial functions tend to apply themes to follow trends and target market segmentation. Stores that sell products using certain themes will have a strong identity and have the opportunity to lead the identity to be wider. Railroad Industrial furniture is an industrial-themed shop in Tegalalang that will be examined the application of the theme in terms of materials, utility settings and other extensive contributions. The representation of industrial themes in Railroad Stores was identified from the use of galvanized iron material, chequer plates, zinc, iron pipes (steampunk style) logo design (industrial-broadway). Identity representation is carried out as a whole from the activities of artisans, art and building products that shelter it into a whole package of branding products. Reuse of used industrial-themed material is a concrete solution which can reduce waste while producing products with high sales value. Adjustment of metal material that dominates the building in terms of utility by making cavities in zinc walls, mounting large fans, exhaust fans and large windows and are helped by the fairly cold ambient temperature in Tegalalang. The choice of industrial themes will greatly contribute as long as it remains with the mindset that utilizes used materials in the industrial field.